The effects of a dentifrice containing a zinc salt and a non-cationic antimicrobial agent on plaque and gingivitis - Saxton, C A; Lane, R M; van der Ouderaa, F (Journal of clinical periodontology, 1987)
The antiplaque potential of metal salts in mouthwashes or dentifrices has been previously demonstrated. The purpose of the present investigation was to establish the effects on plaque and gingival health of a dentifrice which contained a combination of the metal salt, zinc citrate, and the anti-microbial agent, Triclosan. Plaque growth was reduced by a dentifrice which contained either zinc citrate or triclosan, but greater inhibition was achieved with dentifrices which contained both agents. A 4-day non-brushing study in which slurries of the dentifrice were used, confirmed that the test dentifrice which contained 1% zinc citrate and 0.5% Triclosan reduced the accumulation of plaque by 50%. In a double-blind crossover study of 28 days duration, a significant reduction in plaque accumulation and an improvement in gingival health was demonstrated for the test dentifrice compared to the placebo. Further analysis of the data indicated that the dentifrice was most efficacious for participants who brushed ineffectively. Also, the greatest benefit was obtained by subjects that used the largest amount of dentifrice.